Exploiting Seasonal Surplus Energy from Geothermal Utilization for Electrical Power Production - Pálmar Sigurðsson 1990- (2016)
Operation of geothermal power plants is a well-known subject. However, the interaction between heat and power production from seasonal surplus heat have not been investigated at length. This study focuses on exploiting the surplus heat from geothermal combined heat and power (CHP) plants for electrical power production. Nesjavellir geothermal CHP plant in Iceland was used as a case study but the work was structured so it could be implemented for other cases. District heat production at Nesjavellir is highly dependent on seasonal changes in heat load. The amount of seasonal surplus at Nesjavellir was calculated from present demand and estimated for future scenarios. Static thermodynamic models were constructed and optimized for two different bottoming units with the purpose to produce electrical power from heat with variating availability. The bottoming units in question were an organic Rankine cycle (ORC) and a flashing process with a low pressure turbine (LPT). A preliminary feasibility study was performed for both bottoming units. Changes in environmental impact due to a possible bottoming unit at Nesjavellir were addressed and problems with utilizing the seasonal variating heat mentioned. The results from this study indicate that there is an economical feasible way of exploiting the seasonal surplus for electrical power production. Rekstur jarðvarmavirkjana er vel þekkt viðfangsefni. Hins vegar hefur samspilið á milli hitaframleiðslu og raforkuframleiðslu frá umframvarma ekki verið rannsakað ítarlega. Verkefnið fjallar um nýtingu á árstíðabundnum umframvarma frá jarðvarmaverum til framleiðlsu á raforku. Nesjavellir voru teknir til umfjöllunar en verkefnið sjálft var byggt upp með þeim hætti að hægt væri að taka annað jarðvarmaver til skoðunar. Hitaframleiðsla frá Nesjavöllum er háð árstíðabundnum breytingum á hitaþörf. Framboð á umframvarma á Nesjavöllum var reiknað samkvæmt núverandi hitaþörf. Einnig var spáð fyrir um framtíðarmagn af umframvarma. Byggð voru varmafræðileg bestunarlíkön fyrir tvo ...